Linguagens da criança na educação infantil blingue português/inglês: olhando pelo caleidoscópio - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This qualitative-interpretative study, approved by the Ethics Committee, within the approval protocol number 3.219.326, in Plataforma Brasil, has the general objective of understanding how the school organizes its projects in the 3 year old Children class, so that children's linguistic repertoires (multiple and multisensory) are developed in translational practices. In more specific terms, this work seeks to identify the multiple languages of the child considered in the school environment studied, in the Children 3 years class and to identify which social practices the institution promotes to expand the linguistic repertoires of children when building meanings. Such objectives emerged from the problematizing questions: "What linguistic and multisensory constructions can characterize the multiple languages of the child considered in the school environment studied, in the Children 3 years class?" and "Does the political-pedagogical organization of the institution allow social practices that expand linguistic repertoires by building meanings?". The empirical material of the study was generated during 2018, using as sources of generation a questionnaire for the parents of the participating children, partial transcription of the classes recorded on video, notes in the field diary, analysis of the institution's documents (PPP and Anamnesis and Registration Application forms), interview with the Director of the Institution and with the area teachers (Psychomotricity, Capoeira and Musicalization). The context in which this study was developed was a Portuguese/English bilingual child education school in the private network of the city of Goiânia. When investigating the linguistic practices of these children through the lens of Complexity, Decoloniality and Translanguaging, I intend to expand what is known about this phenomenon in the school environment, more specifically in this context and contribute to the construction of knowledge that facilitates action in this important phase of education basic, which is not so widely discussed in the academic world within the area of Languages.I emphasize the social relevance of the study, in the sense of initiating the discussion of complex, decolonial and translilingual practices, in a context hitherto quite colonized, rigid and dichotomized. My look at the empirical material points out that the studied institution offers linguistic education that provides social practices that expand children's linguistic repertoires, which are multiple and multisensory. In this way, the problematizations of the suggested theme contributed to the perception that linguistic education for three-year-old children should go beyond the oral and written language dichotomy, as the child translanguages beyond the two hegemonic codes (Portuguese/English), and it is used in multiple ways to perform its identities and build its senses
Children's languages in portuguese/english bilingual early education: looking through the kaleidoscope
Keywords: Educação Infantil - Educação Bilíngue; Educação Infantil - Práticas translíngues; Child education - Translanguaging Bilingual; Child education - Education practices; CIENCIAS HUMANAS::EDUCACAO